Significance of the combined tests application in serum and liquor of patients with suspected neurosyphilis - Mirković Mihailo; Jovičić Vilma; Basta Ivana; Marjanović Ivan; Lavrnić Dragana (Vojnosanitetski Pregled)
Background. Tertiary syphilis develops in 8-40% of untreated patients. It is most commonly manifested in the form of neurosyphilis, which can be asymptomatic taking the form of tabes dorsalis or progressive paralyze. Nowadays, in the developed countries, progressive paralyze is a rather rare disease, although the incidence of this disease has been rising within the last decades. Case report. We reported a 74-year-old male with the clinical image of dementia showing psychotic symptoms. On cytobiochemical examination of cerebrospinal liquor, hyperproteinorhacmia of 0.70 g/l with the normal number of cells was revealed. Computed tomography of the brain showed the marked cortical cerebral and cerebellar reduction changes with multiple ischemic lesions. Within a routine examination of patients with demention, we performed serologic reactions to syphilis out of which the Veneral Disease Researc Laboratory (VDRL) test in serum and liquor was unreactive, while the Treponema pallidum hemagglutination (TPNA) test in serum and liquor was positive. Positivity in serum and liquor was additionally confirmed by the Western blot method and fluoroscent treponema antibody (FTA) test. The treatment with benzathine fenylpenicilline 2.4 g once weekly resulted in significant improving the psychotic symptoms of the disease even after two weeks. Conclusion. This case report showed that within the differential diagnostics in patients with demention or psychotic disorder it is obligatory to consider syphilis of the nervous system, as well as to apply a combination of various tests which, besides the typical liquor findings, significantly improve the accuracy of diagnosis. Such approach is especially important regarding the fact that neurosyphilis can remain clinically quite asymptomatic for a long period, which could lead to late therapy, while, on the contrary, an adequate and timely treatment can contribute to a significant recovery of any patients.